Isolation and characterization of bacteria from elevator button of UiTM Kuala Pilah / Nur Liyana Najwa Zulkifli - Zulkifli, Nur Liyana Najwa (2018)
The control of microorganisms in university environment is the main concern in order to avoid the spread of infectious diseases. The aim of this study was to isolate, characterize and identify selected bacteria from elevator buttons at academy building of Faculty of Applied Science, Universiti Teknologi MARA (UiTM) Kuala Pilah, Negeri Sembilan. The sample were taken from elevator buttons at academy building. Detection types of bacteria was done on Eosin Methylene Blue Agar, Mannitol Salt Agar and Salmonella Shiegella Agar according the standard microbiological methods. Besides that, Gram-positive and Gram-negative bacteria also were identified by performing gram staining. The research that conducted on 8 buttons from two elevator at academy faculty reveal that all buttons had bacterial contamination with kind of Gram-positive and Gram-negative bacteria. All the buttons was colonized by Staphylococcus aureus and Escherichia coli. Thus from this study it reveal that elevator buttons could lead to the transmission of pathogenic microorganisms, hence it is necessary to clean and disinfectant elevator buttons regularly especially department that has high potential contamination such as elevator that place at laboratories building.